The book of Acts in its ancient literary setting - Winter, Bruce W.; Clarke, Andrew D. (Grand Rapids, MI Eerdmans, 1993)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Acts -- criticism, interpretation, etc